Use of Fingerprints as Authentication of the Applicant's Identity in Notarial Deed Minutes Based on Electronic Systems - Sujiyanto, Daniel Adi; Darmadi, Nanang Sri (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine the practice of notaries in Indonesia, namely the placement of the facer's fingerprints as authentic and vital evidence in various transactions, requiring adaptation to face the challenges of forgery and maintain validity. The placement of the facer's fingerprints emerged as a solution to improve security and legal certainty, using a normative legal approach with a statutory approach method. Then the data was collected from primary legal materials (Notary Law and related regulations), secondary (legal literature and journals), and tertiary (dictionary and legal encyclopedia). Data collection methods include literature studies, field observations, and interviews with competent sources. Data analysis used a qualitative descriptive-analytical method with a deductive-inductive thinking framework. The results of the study show that the Notary Law requires the placement of fingerprints to increase the validity of the deed. Fingerprints, as unique biometrics, provide stronger legal certainty. However, its implementation faces technical challenges (system accuracy, infrastructure), legal (uncomprehensive regulations, personal data protection), and social (public trust, digital literacy). Comprehensive and integrated regulations, which take into account technical, legal and social aspects, are crucial to ensure the effectiveness, security and fairness in the implementation of fingerprinting in the making of notarial deeds.Keywords: Digitalization; Fingerprints; Notary.